Trade openness and income inequality: New empirical evidence. (7th August 2021) - Dorn, Florian; Fuest, Clemens; Potrafke, Niklas
Abstract: We examine how trade openness influences income inequality within countries. The sample includes 139 countries over the period 1970–2014. We employ predicted openness as instrument to deal with the endogeneity of trade openness. The effect of trade openness on income inequality differs across countries. Trade openness tends to disproportionately benefit the relative income shares of the very poor, but not necessarily all poor, in emerging and developing economies. In most advanced economies, trade openness increased income inequality, an effect that is driven by outliers. Our results suggest a strong effect of trade openness on inequality in China and transition countries.